Development of a toolkit to improve interprofessional collaboration and integration in primary care using qualitative interviews and co-design workshops - Sirimsi, Muhammed Mustafa; De Loof, Hans; Van den Broeck, Kris; De Vliegher, Kristel; Van Royen, Paul; Pype, Peter; Driessens, Kristel; Verté, Emily; Remmen, Roy; Van Bogaert, Peter (Frontiers in Public Health, 2023)
Abstract BACKGROUND: Despite numerous attempts to improve interprofessional collaboration and integration (IPCI) in primary care, patients, care providers, researchers, and governments are still looking for tools and guidance to do this more efficiently. To address these issues, we decided to develop a generic toolkit, based on sociocracy and psychological safety principles, to guide care providers in their collaboration within and outside their practice. Finally, we reasoned that, in order to obtain integrated primary care, different strategies should be combined. RESULTS: Ten themes were identified: (i) awareness of the importance of interprofessional collaboration, (ii) the need for a self-assessment tool to measure team performance, (iii) preparing a team to use the toolkit, (iv) enhancing psychological safety, (v) developing and determining consultation techniques, (vi) shared decision making, (vii) developing workgroups to tackle specific (neighbourhood) problems, (viii) how to work patient-centred, (ix) how to integrate a new team member, and (x) getting ready to implement the IPCI toolkit. From these themes, we developed a generic toolkit, consisting of eight modules. CONCLUSION: In this paper, we describe the multiyear co-development process of a generic toolkit for the improvement of interprofessional collaboration. Inspired by a mix of interventions from in and outside healthcare, a modular open toolkit was produced that includes aspects of Sociocracy, concepts as psychological safety, a self-assessment tool and other modules concerned with meetings, decision making, integrating new team members and population health. Upon implementation, evaluation and further development and improvement, this compounded intervention should have a beneficial effect on the complex problem of interprofessional collaboration in primary care.